Survey Estimates of Changes in Alcohol Use Patterns Following the 2012 Privatization of the Washington Liquor Monopoly. (8th February 2018) - Kerr, William C; Williams, Edwina; Ye, Yu; Subbaraman, Meenakshi Sabina; Greenfield, Thomas K
Abstract : Survey-based analyses of alcohol use across Washington's spirits privatization, beer tax reduction and marijuana legalization found no change in alcohol volume, a reduction in spirits volume and a shift to more moderate drinking patterns. Reductions in drinking occurred among marijuana users and those with lower educational attainment reduced spirits volume. Abstract: Aims: The US state of Washington's 333 state-run liquor stores were privatized on 1 June 2012 and purchases began in ~1500 licensed stores of a variety of types. A regime of taxes and fees was implemented to replace the revenues generated by the state stores and, 1 year later, the beer tax was reduced by two thirds. This study evaluates the impact of these changes on total alcohol and spirits consumption in a retrospective pre-test design. Methods: The study sample consists of 2289 adults recruited in three cross-sectional surveys during 2014 and 2015. Retrospective typical past month quantity–frequency measures for before privatization drinking and current past month quantity–frequency measures were compared within subjects, for all alcohol and for spirits only. Results: No change in alcohol volume was seen across privatization while spirits volume was found to decrease, suggesting a shift from spirits to beer. This decline in spirits volume came from a reduction in drinking days while overall drinking days were found to increase. This was offset by a reduction in drinks per drinking day and in heavy occasions. Conclusions: These findings accurately mirror the overall flat trend in per capita alcohol sales but seem to exaggerate the very small shift towards beer seen in sales data. Effects of increased spirits availability appear to have been countered by increased spirits prices and a decreased beer tax, leading to a shift to beer consumption. Short summary: Survey-based analyses of alcohol use across Washington's spirits privatization, beer tax reduction and marijuana legalization found no change in alcohol volume, a reduction in spirits volume and a shift to more moderate drinking patterns. Reductions in drinking occurred among marijuana users and those with lower educational attainment reduced spirits volume.